Favourable ten-year overall survival in a Caucasian population with high probability of hereditary breast cancer - Cortesi, Laura; Masini, Cristina; Cirilli, Claudia; Medici, Veronica; Marchi, Isabella; Cavazzini, Giovanna; Pasini, Giuseppe; Turchetti, Daniela; Federico, Massimo (BMC Cancer, 2010)
The purpose of our study was to compare differences in the prognosis of breast cancer (BC) patients at high (H) risk or intermediate slightly (IS) increased risk based on family history and those without a family history of BC, and to evaluate whether ten-year overall survival can be considered a good indicator of BRCA1 gene mutation.